Pengaruh Current Ratio, Debt To Equity Ratio Dan Net Profit Margin Terhadap Earning Growth Pada Perusahaan Pertambangan Yang Tercatat Di Bursa Efek Indonesia - Zulkifli, Zulkifli (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to examine and analyze the effect of internal earning growth, annual data observation period 2012 until 2015. Type studies quantitative research. The population of all mining companies listed on the Indonesia Stock Exchange and consistently for four years amounted to 26 companies, with non-probability sampling technique is purposive sampling. Analysis data with panel data regression pooled the least square which has value adjusted r-squared 47.8% compared to other models. The results showed that current ratio (CR), debt to equity ratio (DER) and net profit margin (NPM) simultaneously are having the significant influence on the earnings growth. Partially, two variables are the current ratio, debt to equity ratio does not affect earnings growth. Meanwhile, NPM has a negative and significant effect on earning growth. Suggested adding variables external factors, using a sample of companies with other industries.